Hepatitis B vaccination is not yet a reality in supportive health care workers - Poongodi Santhana Kumaraswamy; Palaniappan Nainar; Cinthujah Balachandraperumal; Amudha Vickramathithan Panchapooranam (Journal of the Scientific Society, 2014)
Background: Annual exposure of health care workers (HCWs) to hepatitis B virus infection was estimated world-wide as 5.9%. Hepatitis B though a preventable disease is one of the major causes of morbidity and mortality throughout the world. Objective: This study was carried out to find out the prevalence of hepatitis B surface antigen (HBsAg) among supportive HCWs. Materials and Methods: A total of 115 blood samples were collected from different categories of supportive HCWs, sera were separated, stored at −20°C and tested for HBsAg enzyme-linked immunosorbent assay. Results: Of the 115 HCWs, two were positive for HBsAg. One was female nursing assistant with >20 years experience and the other was male sanitary worker with <20 years experience. Both were above 40 years of age. Conclusion: Proper training of HCWs about universal work precautions, awareness about vaccination, reporting of occupational exposure to health authorities and post-exposure prophylaxis in all health care set ups can be pivotal in preventing health care associated infections.